Eventify : A College Event Organizer App (International Journal of Scientific Research in Science and Technology, 2025)
Eventify, a platform transforming event coordination within academic institution. Crafted to empower educators, Eventify simplifies the event planning process by facilitating effortless event creation, details of event specifics. With an intuitive interface, educators can quickly invite attendees, gather responses[1]. Prioritizing ease of use for learners, Eventify removes the need for manual enrolment, enabling participation with a single swipe on event listings. Students can easily submit feedback surveys and stay updated on event-related information. Eventify serves as a dynamic platform that fosters collaboration and engagement. The backend is powered by Firebase, providing secure and scalable real-time services. Firebase Authentication handles user sign-ins via email or Google accounts, and Firestore efficiently manages data related to events, users, and notifications. Firebase Cloud Messaging (FCM) enables push notifications to keep users informed about the changes[7].
Keywords: Seamless Collaboration; Feedback; Real-Time Updates; Event Listing; Invite Attendees; Notifications